Comparison of Runge-Kutta Methods for Solving Nonlinear Equations - Safaa Abu-Amr; Tebra Almajbri; Mnal Ali (AlQalam Journal of Medical and Applied Sciences, 2024)
This research explores the numerical solutions of nonlinear ordinary differential equations using four distinct methods: Heun method, the Midpoint method, Ralston’s method, and the fourth-order Runge-Kutta method (RK4). Given the complexity and prevalence of nonlinear equations in various scientific fields, effective numerical techniques are essential for obtaining accurate solutions. This research contributes to the understanding of numerical methods in solving complex differential equations, aiding practitioners in selecting the most appropriate approach for their needs. يتناول هذا البحث الحلول العددية للمعادلات التفاضلية العادية غير الخطية باستخدام أربع طرق مميزة: طريقة هيون، وطريقة نقطة المنتصف، وطريقة رالستون، وطريقة رونج-كوتا من الدرجة الرابعة .ونظرًا لتعقيد وانتشار المعادلات غير الخطية في مختلف المجالات العلمية، فإن التقنيات العددية الفعالة ضرورية للحصول على حلول دقيقة. يساهم هذا البحث في فهم الأساليب العددية في حل المعادلات التفاضلية المعقدة، ومساعدة الممارسين في اختيار النهج الأكثر ملاءمة لاحتياجاتهم